Mappe, che passione! - Bernardini, Fulvio (GEOmedia, 2009)
Maps, what a passion! On the base of a blog-ranking proposed by Off the Map last year, this article features a brief review of some interesting web logs dedicated to cartography, web mapping, GIS and technical related issues, neo-cartography, geoweb, geo-visualization and theoretical cartography.